Whole-genome sequencing and characterization of an antibiotic resistant Neisseria meningitidis B isolate from a military unit in Vietnam - Thach Xuan Tran; Trang Thu Le; Long Phi Trieu; Christopher M. Austin; Dong Van Quyen; Huong Minh Nguyen (BMC, 2019)
Abstract Background Invasive meningococcal disease (IMD) persists in military units in Vietnam despite the availability of antibiotics and vaccines. A hindrance to reducing the incidence of IMD in Vietnam is a lack of molecular data from isolates of the causative agent, Neisseria meningitidis from this country. Here, we characterized key genetic and epidemiological features of an invasive N. meningitidis isolate from a military unit in Vietnam using whole-genome sequencing. Methods Neisseria meningitidis was isolated from a conscript admitted for meningitis and tested against seven antibiotics. DNA from the isolate was extracted and sequenced using the Illumina HiSeq platform. Denovo assembly and scaffolding were performed to construct a draft genome assembly, from which genes were predicted and functionally annotated. Genome analysis included epidemiological characterization, genomic composition and identification of antibiotic resistance genes. Results Susceptibility testing of the isolate showed high levels of resistance to chloramphenicol and diminished susceptibility to ampicillin and rifampicin. A draft genome of ~ 2.1 Mb was assembled, containing 2451 protein coding sequences, 49 tRNAs and 3 rRNAs. Fifteen coding sequences sharing ≥ 84% identity with known antibiotic resistance genes were identified. Genome analysis revealed abundant repetitive DNAs and two prophages. Epidemiological typing revealed newly described sequence type, antigenic finetype and Bexsero® Antigen Sequence Typing (BAST). The BAST profile showed no coverage by either Bexsero® or Trumenba®. Conclusions Our results present the first genome assembly of an invasive N. meningitidis isolate from a military unit in Vietnam. This study illustrates the usefulness of whole genome sequencing (WGS) analysis for epidemiological and antibiotic resistance studies and surveillance of IMD in Vietnam.